Analysis of Bullying’ Perpetrators and Victims in Middle Schools in Banjarbaru City, South Kalimantan - Rachman, Ali; Sugianto, Akhmad; Prayudy, Renandra; Ramadhan, M. Rico (Journal of Education Method and Learning Strategy, 2024)
This research is an evaluation of the Indonesian roots program using the Kirkpatrick evaluation model which focuses on evaluating bullying behavior carried out by students in previous years, and victims of bullying at school. The data analysis used is quantitative descriptive. The data obtained from the results of implementing the questionnaire is quantitative data. The results of the study showed that 5 students (36%) had never bullied at school in the previous year's bullying behavior at school. Meanwhile, 9 students (64%) had carried out bullying with a relatively low frequency. Victims of bullying in the previous year reached 64% consisting of 4 male students and 5 female students. The recommendations of this research are: 1) schools should be proactive by creating programs for teaching social skills, problem solving, conflict management and character education. 2) Teachers should monitor changes in students' attitudes and behavior inside and outside the classroom; and there needs to be harmonious cooperation between guidance and counseling teachers, subject teachers, as well as school staff and employees. 3) Parents should collaborate with the school to achieve maximum educational goals without bullying between students at school.